Ocular Manifestations and the Clinical Course of Carotid Cavernous Sinus Fistulas in Asian Patients. (February 2014) - Tan, Anna C. S.; Farooqui, Saadia; Li, Xiang; Tan, Yar Li; Cullen, James; Lim, Winston; Leng, Seah Lay; Looi, Audrey; Tow, Sharon
Abstract Purpose: To study the clinical course with regard to both the angiographic and visual outcomes of carotid cavernous fistulas (CCFs). Background: Carotid cavernous sinus fistulas (CCFs) are conditions which often present with ocular signs and symptoms. The clinical presentation of CCFs is varied according to the anatomy, haemodynamics and size of the CCF. CCFs causing significant symptoms or vision loss should be treated with embolization. Methods: This is a retrospective review of the medical records of all CCF cases seen in the Singapore National Eye Centre from September 2002 to December 2011. Results: 45 patients who had confirmed CCF on conventional cerebral angiography were included. Anterior draining CCFs presented with orbital congestion while posterior draining CCFs presented with pain, diplopia and cranial nerve palsies. Mild residual symptoms were still present in 85% of treated direct CCFs despite complete angiographic closure however 52% of treated dural CCFs had complete resolution of symptoms despite only half of those achieving angiographic closure. Treated and untreated dural CCFs had similar outcomes (87% versus 76% recovered or improved (p > 0.05)). Poor outcomes can result from residual diplopia or vision loss from complications of the CCF itself (e.g. compressive optic neuropathy, glaucoma, retinopathy) or complications from CCF embolization treatment (e.g. central retinal artery occlusion). Conclusion: Presenting symptoms and signs are related to the angiographic drainage of CCFs. Angiographic outcomes after embolization treatment may not always correlate with clinical outcomes.